Дослідження та розробка стратегії оптимізації та підвищення продуктивності веб-додатків на базі NodeJS та React з використанням штучного інтелекту - Дробицький, Д. С. (ХНУРЕ, 2024)
This study focuses on the development of web applications based on NodeJS and React technologies, which have become integral components of the digital paradigm, with their performance and optimization emerging as strategically important tasks. The integration of Artificial Intelligence (AI) into this ecosystem can interact with existing technologies, contributing to their enhancement and evolution.
Keywords: NodeJS; React; веб-додаток; штучний інтелект; AI